Resistance training volume load with and without exercise displacement - Hornsby, W. G.; Gentles, J. A.; Comfort, P.; Suchomel, T. J.; Mizuguchi, S.; Stone, M. H. (Sports, 2018)
Monitoring the resistance training volume load (VL) (sets × reps × load) is essential to managing resistance training and the recovery-adaptation process. Subjects: Eight trained weightlifters, seven of which were at national level, participated in the study. Methods: VL was measured both with (VLwD) and without (VL) the inclusion of barbell displacement, across twenty weeks of training, in order to allow for comparisons to be made of these VL calculating methods. This consisted of recording the load, repetition count, and barbell displacement for every set executed. Comparisons were made between VL and VLwD for individual blocks of training, select training weeks, and select training days. Results: Strong, statistically significant correlations (r = 0.78, p < 0.001) were observed between VL and VLwD between all training periods analyzed. t-tests revealed statistically significant (p = 0.018) differences between VL and VLwD in four of the seven training periods analyzed. Conclusion: The very strong relationship between VL and VLwD suggest that a coach with time constraints and a large number of athletes can potentially spare the addition of displacement. However, differences in percent change indicate that coaches with ample time should include displacement in VL calculations, in an effort to acquire more precise workload totals.